Polyamines as constituents of the outer membranes of Escherichia coli and Salmonella typhimurium. - Koski, P (1991)
Extraction of whole cells of Salmonella typhimurium and Escherichia coli with 1 M NaCl released 8 to 13% of their total cellular polyamines (putrescine, cadaverine, and spermidine). This extraction did not cause significant cell lysis, release of outer membrane (OM) constituents, or leakage of periplasmic beta-lactamase. The extraction released nearly equal amounts of polyamines from mdo (membrane-derived oligosaccharide) mutants and wild type. These findings suggest that the released polyamines are apparently bound to the cell envelope. NaCl (1 M) was as effective as trichloroacetic acid in releasing polyamines from isolated OM and lipopolysaccharide (LPS). Isolated OM contained four times more polyamines than the cytoplasmic membrane. The increased binding to the OM is apparently due to the association of polyamines with the polyanionic LPS. Nearly identical amounts of polyamines were found in the OM and LPS preparations (as quantified per milligram of LPS). These amounts are equal to those released from the intact cells by 1 M NaCl (quantitation as above). However, redistribution of polyamines took place after cell disruption, because the relative proportions of different polyamines varied in the OM and LPS preparations. These results indicate that polyamines released from intact cells during 1 M NaCl extraction are preferentially derived from the OM.